Sistem Informasi Pendataan Karyawan Pada PT. Waskita Karya Banda Aceh - Ulis S, Maria Tiarma; Ihsanuddin; Imilda (Computer Journal, 2024)
The employee information system is a data processing tool developed for PT. Waskita Karya to improve the management and accessibility of employee records. This study addresses employee data management issues at the company and proposes a system design using PHP and MySQL. The objective is to optimize employee data management and streamline processes using a web-based application. Data for the study were gathered through literature review and field observations, including interviews and direct observation of relevant subjects. The system development followed the waterfall methodology, progressing through stages of requirement analysis, system design, implementation, testing, and maintenance. The employee information system is managed by administrative staff and aims to provide a faster, more efficient, and accurate data processing solution. Based on the research, it is concluded that the new system adheres to company procedures and significantly enhances the data management process by utilizing PHP and MySQL.